2018
DOI: 10.1002/slct.201802348
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Based Sulfide Materials for Batteries

Abstract: Metal sulfide materials with high specific capacity, good cyclic and rate performance become a hot spot in the research of batteries. As one of the important representatives, nickel-based sulfide nanomaterials with good electronic conductivities and a high capacity already have attracted a lot of publicity in terms of battery devices. Based on the current most advanced research, this review mainly introduces some synthetic methods and the applications of nickel-based sulfide nanomaterials in lithium ion batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…[44][45][46] There are some reviews focusing on Ni-based materials for supercapacitor applications. [47,48] Besides, Ni-based materials have also been reported as cathodes for rechargeable batteries. Xu et al [49] discussed the layered Ni-based oxides as LIB cathodes, including unsubstituted LiNiO 2 , LiNi 1-x TM x O 2 , and LiNi 1-x-y TM x TM' y O 2 components based on different material designs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46] There are some reviews focusing on Ni-based materials for supercapacitor applications. [47,48] Besides, Ni-based materials have also been reported as cathodes for rechargeable batteries. Xu et al [49] discussed the layered Ni-based oxides as LIB cathodes, including unsubstituted LiNiO 2 , LiNi 1-x TM x O 2 , and LiNi 1-x-y TM x TM' y O 2 components based on different material designs.…”
Section: Introductionmentioning
confidence: 99%
“…There are some reviews focusing on Ni‐based materials for supercapacitor applications. [ 47,48 ] Besides, Ni‐based materials have also been reported as cathodes for rechargeable batteries. Xu et al.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are some reviews focusing on nickel-based materials. In the previous reports, nickel-based materials for rechargeable batteries were discussed in detail, including anodes and cathodes for LIBs and SIBs, cathode hosts and separators for LSBs, cathodes for Ni-based aqueous batteries, catalysts for MABs, and nickel-based sulfide nanomaterials for batteries. , However, few reviews focused on nickel-based electrode materials for the whole secondary battery systems (including KIBs, MIBs, and AlBs). Besides, as illustrated in Figure b, the publications on nickel-based electrode materials have rocketed obviously.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tremendous effort has been devoted to develop earth-abundant materials that can substitute Pt in HER [5,6]. Among those, TMS (transition metal sulfides), such as nickel sulfides, appear to be a promising class of HER electrocatalysts owing to their earth abundance, remarkable HER performance, and long-term operational stability in both acidic and alkaline solutions [7][8][9][10][11][12]. For example, T. F. Hung et al reported that the nickel sulfide nanostructure showed high electrochemical performance in HER and supercapacitors [13,14].…”
Section: Introductionmentioning
confidence: 99%